PENGARUH KECERDASAN EMOSIONAL DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASI DI SMP NEGERI KECAMATAN TAMAN PEMALANG (Studi Pada Guru PNS SMP Di Kecamatan Taman Kabupaten Pemalang) - Eko Gunawan, 1352020045; Fauzan, Mohammad (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study examined the effects of emotional intelligence and professional competence of the teachers performance organizational culture moderated in junior high school districts Pemalang Park. The study population was junior high school teachers in the district park totaling 155 people. In this study, using primary data obtained by questionnaire. Engineering analysis using statistical program SPSS version 22. The results showed that emotional intelligence and professional competence have a positive and significant impact on teacher performance. In this research, organizational culture does not have a significant positive influence and not on teacher performance and organizational culture are not moderate the influence of emotional intelligence, the professional competence of the teachers performance.Keywords: Organizational Culture, Emotional Intelligence, Professional Competence